2020
DOI: 10.1017/aae.2020.23
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Economically Optimal Levels of Nitrogen Fertilizer in No-Tillage Continuous Corn

Abstract: Stochastic plateau production functions provide improved fertilizer recommendations based on multi-year agronomic experiments where weather and other stochastic variables change over time. This research assesses the profitability of no-tillage corn production in northeastern Colorado and determines economically optimal nitrogen fertilizer rates. It also proposes an alternative parameterization of the linear response stochastic plateau model which provides a robustness check against traditional parameterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Since in 2018 (study 1) no significant differences were observed from 202 kg N ha −1 to 314 kg N ha −1 for either the BMP or TMP with the same plant population, in 2019 (study 2) and 2020 (study 3) the experiment was repeated in those same plots, except with 2 levels of crop row spacing (38.1 and 76.2 cm) and 2 levels of N application (0 and 202 kg urea N ha −1 ) (Table 1). This response to N rate from study 1 agrees with findings from Villacis et al [31] that reported profit-maximizing N rates ranging from 162 to 197 kg N ha −1 for continuous no-till corn planted at 76.2 cm row spacing.…”
Section: Methodssupporting
confidence: 90%
“…Since in 2018 (study 1) no significant differences were observed from 202 kg N ha −1 to 314 kg N ha −1 for either the BMP or TMP with the same plant population, in 2019 (study 2) and 2020 (study 3) the experiment was repeated in those same plots, except with 2 levels of crop row spacing (38.1 and 76.2 cm) and 2 levels of N application (0 and 202 kg urea N ha −1 ) (Table 1). This response to N rate from study 1 agrees with findings from Villacis et al [31] that reported profit-maximizing N rates ranging from 162 to 197 kg N ha −1 for continuous no-till corn planted at 76.2 cm row spacing.…”
Section: Methodssupporting
confidence: 90%
“…The estimates used were those for the stochastic linear response plateau function from continuous corn. Estimates by Villacis et al (2020) were similar.…”
Section: Yield-monitor Datamentioning
confidence: 61%
“…Finger (2012) and Meyer-Aurich et al (2020) found that nitrogen taxes reduce N fertiliser levels and thus reduce N emissions from agriculture. While Villacis et al (2020) found that the profit-maximising nitrogen rates ranged from 162 to 197 kg/ha for fertiliser prices of $0.72, $0.96 and $1.20.…”
Section: Discussionmentioning
confidence: 99%